GUTTA TAMARIND: OLAHAN VISUAL BAHASA RUPA MENGGUNAKAN MATERIAL RAMAH LINGKUNGAN - Iman Budiman; Alya, Shopia Himatul; Pandanwangi, Ariesa (Institut Bisnis dan Teknologi Indonesia, 2022)
Painting has undergone many developments. One of them is technical development in terms of materials. One of the unique techniques in painting is the gutta tamarind technique which uses ground tamarind seeds that are ground. This study aims to examine the use of tamarind seeds as an alternative medium in the work. Gutta tamarind is popular because the material used resembles the material for batik. However, in the process of using it, gutta tamarind which is also known as cold wax does not require a heating stove like the hot wax of batik in general. In this study, we will discuss the process of making cold wax from tamarind seed powder. This study uses a qualitative descriptive research method by studying the manufacture of cold wax gutta tamarind in stages. The results of this study indicate that the gutta tamarind technique in the process of making textile paintings or wastra paintings produces characters that are no less unique and beautiful.